Keratin intrinsic fluorescence as a mechanism for non-invasive monitoring of its glycation. (1st January 2023) - Muir, Rhona; Forbes, Shareen; Birch, David J S; Vyshemirsky, Vladislav; Rolinski, Olaf J
Abstract: We have studied the evolution of keratin intrinsic fluorescence as an indicator of its glycation. Steady-state and time-resolved fluorescence of free keratin and keratin-glucose samples were detected in PBS solutions in vitro . The changes in the fluorescence response demonstrate that the effect of glucose is manifest in the accelerated formation of fluorescent cross-links with an emission peak at 460 nm and formation of new cross-links with emission peaks at 525 nm and 575 nm. The fluorescence kinetics of these structures is studied and their potential application for the detection of long-term complications of diabetes discussed.